Meat and bone meal stimulates microbial diversity and suppresses plant pathogens in asparagus straw composting - Liu, Xinxin; Li, Xiaoxiao; Hua, Yinfeng; Sinkkonen, Aki; Romantschuk, Martin; Lv, Yanfang; Wu, Qian; Hui, Nan (Frontiers in Microbiology, 2022)
Meat and bone meal (MBM), as slaughterhouse waste, is a potential biostimulating agent, but its efficiency and reliability in composting are largely unknown. To access the MBM application to the composting process of asparagus straw rice, we followed the composting process for 60 days in 220-L composters and another 180 days in 20-L buckets in treatments applied with MBM or urea. The microbial succession was investigated by high-throughput sequencing. Compared with urea treatments, MBM addition stabilized pH and extended the thermophilic phase for 7 days. The germination index of MBM treatments was 24.76% higher than that of urea treatments. MBM also promoted higher microbial diversity and shifted community compositions. Organic matter and pH were the most significant factors that influence the bacterial and fungal community structure. At the genus level, MBM enriched relative abundances of organic matter-degrading bacteria (Alterococcus) and lignocellulose-degrading fungi (Trichoderma), as well as lignocellulolytic enzyme activities. Notably, MBM addition decreased sum abundances of plant pathogenic fungi of Phaeoacremonium, Acremonium, and Geosmithia from 17.27 to 0.11%. This study demonstrated the potential of MBM as an effective additive in asparagus straw composting, thus providing insights into the development of new industrial aerobic fermentation.